Rice Wine Fermentation: Unveiling Key Factors Shaping Quality, Flavor, and Technological Evolution - Baoyu Peng; Haiyang Huang; Jingjing Xu; Yuan Xin; Lang Hu; Lelei Wen; Li Li; Jinwen Chen; Yu Han; Changchun Li (Foods)
Rice wine, as a traditional fermented beverage, has its quality and flavor influenced by a combination of multiple factors. This review provides an overview of the key aspects of rice wine production, including raw material selection and processing, the regulation of quality by brewing techniques, the mechanisms of microbial community interaction during fermentation, and the types and formation mechanisms of major compounds in rice wine (including flavor compounds and non-volatile components). The study highlights that different raw materials and processing methods significantly impact the fundamental flavor profile of rice wine, while fermentation conditions and dynamic changes in microbial communities determine its flavor complexity and stability. Additionally, this review examines various factors affecting the quality and flavor of rice wine, such as fermentation environment, microbial metabolism, and control of harmful substances, and summarizes modern research and technological advancements, emphasizing the potential of digital and intelligent technologies in enhancing the quality and safety of rice wine. Finally, future research directions are proposed to promote modernization and quality improvement of the rice wine industry.